(3OjhGf GHf MLQ GdYSbdGfj (B((3efXhe GdOQQ(B)s - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3djMPQ GdeA GdoeNGda CeQg ef aJfI Ch ef YPGH jDde Ph GdeYLRGJ GdHGgQGJ aSd HgG fWb GdMUG hHgGFekG bO cdehG s
(3BNQgG (B:s
(3fXQJ deG SWQJg ef eLGeY dgG GdaVd EPG QGbJ eMGSfgG oJYRi s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B80 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B765s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs